Identification of slow-wave ion cyclotron emission on JT-60U. (6th October 2021) - Sumida, S.; Shinohara, K.; Ichimura, M.; Bando, T.; Bierwage, A.; Ide, S.
Abstract: Ion cyclotron emissions (ICEs) are generally considered to be emissions of fast waves driven by velocity-space instabilities due to fast ions. However, on JT-60U, measured properties of ICEs observed at frequencies lower than the bulk ion cyclotron frequency (L-ICEs) do not match the fast-wave dispersion relation, indicating the possibility of L-ICEs being slow-wave emissions. In this paper, we show that L-ICE observation on JT-60U can be explained in terms of a slow-wave emission driven by fast ions, i.e. a slow-wave ICE. To investigate whether the slow wave can be driven by fast ions, its linear growth rate has been calculated in a typical discharge using a wave dispersion code. This wave dispersion code is capable of performing calculations with an arbitrary spatially-localized velocity distribution. For the growth rate calculation, we have directly used fast ion velocity distributions evaluated by an orbit following Monte-Carlo simulation. It is found that negative-ion-source neutral beam (N-NB) injected fast ions can destabilize the slow wave. Its frequency and wavenumber at high linear growth rates are close to experimental observations of L-ICE. In addition, observed L-ICE frequencies agree reasonably well with frequencies based on the slow-wave dispersion relation at measured toroidal wavenumbers in several discharges. Moreover, the observed frequencies also agree with the Doppler-shifted cyclotron resonance frequencies for the N-NB injected ion. Therefore, L-ICE in JT-60U is identified as a slow-wave ICE driven by the N-NB injected fast ions and distinguished from other ICEs through a measurement of its frequency and wavenumber.